The Undergraduates’ Perceptions About Learning Public Speaking Online by Using Zoom - Kinasih, Tita (RETAIN, 2021)
Speaking is one of the English language skills that must be taught to students. However, due to the Covid-19 outbreak, the government ordered schools including universities to conduct online learning. One of the platforms used by universities to support their online learning was using Zoom. The aims of this research were to describe the student’s perception about the implementation of online learning by using Zoom in Public Speaking class and about the use of Zoom as a learning tool to learn speaking. This research used survey research and involved 56 students from 2rd semester as respondents. The results of this research indicated that for students' perceptions of the application of online learning using Zoom in public speaking classes, students agreed with some statements that online learning via Zoom was suitable for the current situation because it could smooth the learning process, thus students enjoyed the learning process and felt involved in the class. Meanwhile, related to students' perceptions of the use of Zoom as a learning tool for public speaking classes, students responded with positive results or agreed to all of the components given, more clearly explained in the results and discussion.